Double Ionic–Electronic Transfer Interface Layers for All‐Solid‐State Lithium Batteries. Issue 34 (13th July 2021) - Zheng, Jingang; Sun, Chengguo; Wang, Zhenxing; Liu, Shaojun; An, Baigang; Sun, Zhenhua; Li, Feng
Abstract: Large‐scale implementation of all‐solid‐state lithium batteries is impeded by the physical limitations of the interface between the electrode and solid electrolyte; specifically, high resistance and poor stability, as well as poor compatibility with Li + migration. We report double ionic–electronic transfer interface layers grown at electrode–electrolyte interfaces by in situ polymerization of 2, 2′‐bithiophene in polyethylene oxide (PEO) electrolyte. For all‐solid‐state LiFePO4 ∥PT‐PEO‐PT∥Li cells, the formation of a conductive polythiophene (PT) layer at the cathode–electrolyte interface resulted in an at least sevenfold decrease in interface resistance, and realized a capacity retention of about 94 % after 1000 cycles along with a lower polarization voltage under a rate of 2 C. The mixed ionic–electronic conductive layers imparted superior interface stability and contact while keeping good compatibility with the Li anode. Abstract : The double ionic–electronic transfer interface layers between electrode and electrolyte were created by in situ polymerization of 2, 2′‐bithiophene inside the solid‐state lithium battery, resulting in low interface resistance and highly stable interface contact.